News Framing of Assets of Trading Victim Indra Kenz Seized by the State - Frisila Ayu Fitriyanti; Athok Murtadhlo (DIGICOM : Jurnal Komunikasi dan Media, 2023)
This research aims to understand how the TVOneNews television media constructs news about the fate of the assets of the victim of illegal trading on Binomo, Indra Kenz, being seized by the state. Because Indra Kenz, the victim of illegal trading on Binomo, was judged as a gambler by the judge, and the assets were confiscated by the state. According to experts in the Anti-Money Laundering Act (TPPU), there were no gambling charges filed, only charges of money laundering against Indra Kenz. The purpose of this research is to examine how the "Apa Kabar Indonesia Malam" program on tvOneNews constructs the issue of justice for the victim regarding the judge's decision to label them as a gambler. The research uses Robert N. Entman's framing analysis method and a qualitative research approach with a constructivist perspective. It is analyzed through four elements, including defining the problem, diagnosing causes, making moral judgments, and providing treatment recommendations. Data collection techniques involve video documentation from special reports on the "Apa Kabar Indonesia Malam" program. The research results indicate that mass media is a loaded industry and a business institution that is not always objective. Therefore, the outcomes of mass media, such as TV programs and news texts, are influenced by media personnel and ownership. Here, Putri Viola on "Apa Kabar Indonesia Malam" constructs the issue of justice for victims of illegal trading on Binomo, Indra Kenz, for law enforcement purposes.